2022
DOI: 10.1186/s12934-022-01751-2
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin production by an oleaginous fungus, Aspergillus terreus KPR12 using sago processing wastewater (SWW)

Abstract: Background Lovastatin is one of the first statins to be extensively used for its cholesterol-lowering ability. It is commercially produced by fermentation. Species belonging to the genus Aspergillus are well-studied fungi that have been widely used for lovastatin production. In the present study, we produced lovastatin from sago processing wastewater (SWW) under submerged fermentation using oleaginous fungal strains, A. terreus KPR12 and A. caespitosus ASEF14. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…The maximum production of lovastatin of 360 mg L−1 was observed. A. terreus KPR12 produced a maximum lovastatin yield of 450.79 mg L −1 which was reported by Srinivasan et al 33 . Mahmoud and Hadi reported Laetioporus sulphurous which was reported to produce maximum lovastatin of about 280μg/ mL 40 .…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The maximum production of lovastatin of 360 mg L−1 was observed. A. terreus KPR12 produced a maximum lovastatin yield of 450.79 mg L −1 which was reported by Srinivasan et al 33 . Mahmoud and Hadi reported Laetioporus sulphurous which was reported to produce maximum lovastatin of about 280μg/ mL 40 .…”
Section: Discussionsupporting
confidence: 76%
“…This is achieved by reducing the pH and lactonization form. Therefore, producing lovastatin in an acidic medium is required 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This enzyme was involved in the synthesis of mevalonate, an intermediate metabolite in the synthesis of ergosterol (main components of the fungal membrane) and cholesterol. Thus, since lovastatin has a lipid origin (statin family), it could be related to the ergosterol synthesis pathway [31,43,51,52,55]. Currently, this could be the answer to the increase in lipid production at 96 h of incubation of the A. terreus bio lm in this work.…”
Section: Cns Aspergillosis Is Commonly Reported In Middle Eastern Cou...mentioning
confidence: 83%
“…It was shown that around 24 hours an early maturation occurs, and around 48 and 72 hours respectively, a decrease in the bio lm formed with a statistically representative later elevation was shown. Likewise, it is possible to link a similar behavior to the logarithmic phase and the lag phase (adaptation) in conventional microbial growth kinetics, like that described for A. fumigatus bio lm [41][42][43][44]. The decrease in fungal bio lm formation between 24 and 48 hours (Fig.…”
Section: Cns Aspergillosis Is Commonly Reported In Middle Eastern Cou...mentioning
confidence: 95%